Identification of Acoustic-Vibratory System by Acoustic Measurement - Takuzo Iwatsubo; Shozo Kawamura; Masahito Kamada (Shock and Vibration)
A new method for reducing ill-conditioning in a class of identification problems is proposed. The key point of the method is that the identified vibration of the sound source is expressed as a superposition of vibration modes. The mathematical property of the coefficient matrix, the practical error expanding ratio, and the stochastic error expanding ratio are investigated in a numerical example. The mode-superposition method is shown to be an effective tool for acoustic-vibratory inverse analysis.